Waiver of wife’s legacy and its impact on the validity of marriage contract in Islam - Almabrouk, Mahdi Amin Mousa; Muhammad Husni, Ahmad; El-Seoudi, Abdel Wadoud Moustafa Moursi (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
This research paper tries to explore the law of legacy as well as waiver of legacy and its impact on the validity of marriage contract. The objective of this study is to know whether waiver of legacy is acceptable in Islamic Law and to how extent it could affect the validity of the marriage contract. Deductive qualitative data analysis of verses of Al-Quran and of texts of Hadith was employed to answer two research questions: do husband and wife have the right to waive their right of legacy before signing the contract? What is the impact of this condition on the validity of the contract of marriage? Finding showed that husband and wife do not have the right to waive legacy of each other and the condition of waiver of legacy is invalid but the marriage contract is valid.